(untitled) (Indian Journal of Nematology, 2024)
The compatibility of six multi-facial biocontrol isolates of Trichoderma species, viz., Trichoderma harzianum AMUTH-1, T. harzianum AMUTH-2, T. harzianum AMUTH-3, T. asperellum (= T. viride) AMUTV-1, T. asperellum AMUTV-3 and T. virens (= Gliocladium virens) AMUTS-1 with two non-fumigant nematicides, fluensulfone and fluopyram was tested in vitro. Both nematicides were tested by the poisoned food method and the compatibility was evaluated at six different concentrations (10, 25, 50, 100, 200, and 500 ppm). The highest concentration of nematicide at which the lowest inhibition of Trichoderma isolates was regarded as the maximum tolerance concentration (MTC). Among Trichoderma isolates, T. harzianum AMUTH-1 showed the highest compatibility with an MTC value of 500 ppm toward fluopyram. The next MTC was observed with T. asperellum AMUTV-3 (500 ppm fluopyram and 200 ppm fluensulfone), followed by T. harzianum AMUTH-3 (500 ppm fluopyram and 200 ppm fluensulfone) and T. virens AMUTS-1 (25 ppm fluopyram and 10 ppm fluensulfone). The isolate T. asperellum AMUTV-1 exhibited the lowest MTC toward both nematicides, i.e., 10 ppm. Overall, fluopyram was more compatible with the above Trichoderma isolates than fluensulfone. The study demonstrated the compatibility of fluopyram and fluensulfone with six isolates of Trichoderma spp. and their MTCs were up to 500 ppm, which was significantly higher than the recommended doses of both nematicides. Therefore, it is inferred that the efficiency of the aforementioned Trichoderma isolates will not be impacted by nematicidal use at the above concentration and both the nematicides can be applied in conjugation with biopesticides (Trichoderma isolates) under integrated nematode management for the plant parasitic nematodes.